From Blofeld to Moneypenny : gender in James Bond - Gerrard, Steven (Emerald studies in popular culture and gender, 2020)
The world of James Bond is complex and ever growing. The British secret agent started off life as a semi-fictional, part-biographical character in Ian Fleming's 1953 novel, Casino Royale. Since then, 007 has captured the minds and hearts of a worldwide audience, and the franchise is now available over multiple media platforms, including movie, comic strips, games, graphic novels and fashion statements. This edited collection examines the role that gender has played across the platforms that the James Bond franchise now occupies. Each chapter investigates gender-approaches through a variety of case studies, including Bond, his boss M, and Miss Moneypenny, the songs and title sequences, the villains, computer games, 'Lad's Mags', and the fashions of the era. Looking beyond the Bond Girl, expert editor Steven Gerrard brings together a cast of contributors that investigate not only femininity, but also masculinity when it comes to the world's best-known agent - a man with a license to kill. In a rapidly changing world where gender boundaries are being eroded, this edited collection investigates the changing and challenging roles that gender has undergone in the franchise. By using a series of case studies, and employing theoretical modes linked to close analysis, each chapter clearly demonstrates how and why the world of James Bond is important in reflecting the changing gender roles within modern society.